Method for detecting content of functional groups on surfaces of magnetic particles
UV spectroscopy detects the absorbance of easily leaving groups on magnetic particles, and combines fluorescent derivatization reagents such as Fmoc to react with functional groups, which solves the problems of large detection errors and height limits in the prior art, and realizes high sensitivity and stability detection of functional groups on the surface of magnetic particles.
Patent Information
- Application Number
- CN202311415766.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-30
- Publication Date
- 2025-05-02
AI Technical Summary
The existing methods for detecting the functional group content on the surface of magnetic particles have problems such as large testing errors, high detection limits, high cost, complex operation, and low efficiency. In particular, it is impossible to accurately measure the hydroxyl group in the presence of carboxyl groups.
Ultraviolet spectroscopy is used to detect the absorbance at a specific wavelength of the easily departed group coupled to magnetic particles, and a heterophase detection method for the surface functional groups of magnetic particles is established by reacting fluorescent derivatization reagents such as Fmoc.
Quantitative analysis of trace hydroxyl and carboxyl groups on the surface of magnetic microspheres is realized, with small test errors, low detection limits, simple operation and low cost, and is suitable for polymer-coated magnetic particles with trace amounts of surface functional groups.
Smart Images

Figure BDA0004519465230000021 
Figure BDA0004519465230000031 
Figure BDA0004519465230000061
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of analytical chemistry, and in particular relates to a method for detecting the content of functional groups on the surface of magnetic particles. Background Art
[0002] Magnetic microspheres are a composite of organic polymers and inorganic magnetic substances. They have many surface functionalities of organic polymer microspheres and magnetic responsiveness of magnetic inorganic substances. Since the mid-1970s, the application research of magnetic polymer microspheres in many fields such as cell separation, protein purification, immobilized enzymes, nucleic acid research, targeted drugs, environmental / food microbial detection, etc. has been increasing. If its surface functionality is to be utilized, it is necessary to coat the surface of the magnetic microspheres with polymers so that they carry the desired functional groups such as hydroxyl and carboxyl to improve and expand its application range. However, the carboxyl and hydroxyl contents of commercial magnetic particles are currently at the μmol / g level, and they have great application prospects in the downstream IVD in vitro diagnosis and chemiluminescence fields. This requires the analysis method to be at the trace and ultra-trace level, and at the same time requires the detection to be fast, sensitive and stable.
[0003] At present, the method for determining the carboxyl content on the surface of magnetic particles is mainly conductivity titration. Chemical analysis uses the principle of ion exchange to make the chemical reaction between the reagent and the carboxyl group, thereby directly or indirectly quantitatively determining the carboxyl content. For example, the commonly used acid-base titration and Boehm titration methods have a measurement accuracy of mmol / g; instrumental analysis methods mainly include TG-FTIR (thermogravimetric-Fourier transform infrared spectroscopy) analysis, GC (gas chromatography) and XPS (X-ray photoelectron spectroscopy).
[0004] However, existing detection methods generally have large test errors: the presence of hydroxyl groups affects the titration effect of carboxyl groups. At the same time, during the titration process, factors such as the selection of titrants and indicators, and the control of titration speed may introduce errors (5-11%), affecting the accuracy of the results, and it is impossible to accurately determine hydroxyl groups in the presence of carboxyl groups. At the same time, it is also accompanied by problems such as high detection limits, high costs, complex operations, and low efficiency. Summary of the invention
[0005] In view of the defects of the prior art, the present invention provides a method for detecting the content of functional groups on the surface of magnetic particles. The present invention uses ultraviolet spectroscopy to detect the absorbance at a specific wavelength of the easy-leaving group coupled to the magnetic particles, which can accurately detect the carboxyl content on the surface of the magnetic particles and has great technical feasibility and application prospects.
[0006] Taking 9-fluorenylmethoxycarbonyl protecting group (Fmoc) as an example, it is a commonly used fluorescent derivatization reagent. It has no fluorescence itself, and only after reaction can a highly sensitive and stable fluorescent derivative be obtained. Therefore, a heterogeneous detection method for functional groups on the surface of magnetic particles can be established by utilizing the principle that Fmoc itself has fluorescence and can react with functional groups. In principle, it is applicable to the determination of all material surfaces.
[0007] A method for detecting the content of functional groups on the surface of magnetic particles, wherein the functional groups are hydroxyl groups and / or carboxyl groups, and the detection method comprises the following steps: A. Preparation of standard curve: (A1) Weigh 10-20 mg of UV leaving base into a 50 mL volumetric flask, dissolve it in 5 mL of dissociation agent, place it on a shaker at 25 °C for 30 min, and make up to volume with methanol; (A2) Add 1 mL of the solution obtained in step (A1) to a 10 mL volumetric flask, add 0.9 mL of dissociation agent, and then make up to volume with methanol to obtain a standard curve test solution; (A3) Take 1 mL of dissociation agent to a 10 mL volumetric flask and dilute to volume with methanol to obtain a blank control; (A4) at 300 nm, measure the absorbance Ai of the standard curve test solution under the blank control to obtain a single-point calibration curve; and obtain the calculation formula of the functional group content as follows: Wherein: b is the sample dilution multiple, M is the molecular weight of the UV leaving group, Mi is the mass of the UV leaving group, in mg; Ai is the absorbance of the UV leaving group, in A; M0 is the mass of the magnetic particle sample, in mg; A0 is the absorbance of the magnetic particle sample, in A; B. Sample testing: (B1) Weigh 50-100 mg of magnetic particle sample into a test tube, add 16-36 mg of UV leaving group, 16-38 mg of condensing agent, 1-2 mL of DMF, and 6-12 mg of catalyst in sequence, seal, ultrasonically disperse for 2-10 min, and then shake at 25° C. for 1-3 h; (B2) Add 5-10 mL of organic solvent to the test tube, ultrasonicate for 2 min, magnetically absorb the magnetic particles to the bottom of the test tube, and pour out the upper solution, and wash repeatedly until the absorbance of the upper solution at a wavelength of 300 nm is less than 0.07, and the absorption error of the two washings is within ±0.005, which determines that the washing is complete, and magnetically recover the magnetic particles and pour out the upper solution; (B3) drying the recovered magnetic particles; (B4) Weigh 10-20 mg of dried magnetic particles into a volumetric flask, add 1-2 mL of dissociation agent, shake and react at 25°C for 30-60 min, then make up to volume with methanol, filter with a 0.2-1 μm filter membrane, and measure the absorbance value, which is the absorbance value A0 of the magnetic sphere sample. Substitute it into the above formula to calculate the content of functional groups.
[0008] Preferably, the functional group is a hydroxyl group, and the UV leaving group is any one of Fmoc-Leu-OH, Fmoc-Ala-OH, Fmoc-Cys(Trt)-OH, Fmoc-Lys(Boc)-OH, and Fmoc-Asp(otBu)-OH.
[0009] Preferably, the UV leaving group is Fmoc-Leu-OH, the condensing agent is MSNT, and the catalyst is Melm.
[0010] More preferably, the functional group is a hydroxyl group, and the amount of the condensing agent added is 19-38 mg.
[0011] Preferably, the functional group is a carboxyl group, and the UV leaving group is any one of Fmoc-EDA.HCl, Fmoc-Cl, and Fmoc-N-Me-EDA(N-Me).HCl.
[0012] Preferably, the UV leaving group is Fmoc-EDA.HCl, the condensing agent is HBTU, and the catalyst is DIEA.
[0013] More preferably, the functional group is a carboxyl group, and the amount of the condensing agent added is 16-32 mg.
[0014] Preferably, the dissociating agent is a piperidine-DMF solution with a concentration of 20-50%.
[0015] Preferably, the organic solvent is acetonitrile, tetrahydrofuran, dioxane, acetone, ethanol or methanol.
[0016] Preferably, the filter membrane is made of PES, MCE, NYLON, PP, PTFE or PVDF.
[0017] This method realizes the quantitative analysis of trace hydroxyl and carboxyl groups on the surface of magnetic microspheres. In the determination process, the detection reagent is separated from the analyte, and the detection can be completed by only measuring the supernatant of the reagent. The test error is small, the detection limit is low, the operation is simple, the cost is low, the range of raw materials can be selected, the detection result is highly reproducible, and it is suitable for polymer-coated magnetic particles with trace surface functional groups that are difficult to detect directly.
[0018] Advantages of the present invention: (1) Only the reagent in the supernatant needs to be measured, and the magnetic particles are not directly involved in the detection. This method is suitable for the functional group content on the surface of the solid support which is difficult to measure. (2) Within the nmol / L concentration range, there is a good linear relationship between the UV absorbance value and concentration of the Fmoc-piperidine adduct, and the detection sensitivity is high. DETAILED DESCRIPTION
[0019] Example 1 The content of carboxyl groups in the magnetic particles was determined as follows: A. Preparation of standard curve: (A1) Weigh 19.1 mg of Fmoc-EDA.HCl into a 50 mL volumetric flask, dissolve it in 5 mL of 20% piperidine-DMF solution, place it on a shaker at 25°C for 30 min, and make up to volume with methanol; (A2) taking 1 mL of the solution obtained in step (A1) into a 10 mL volumetric flask, adding 0.9 mL of 20% piperidine-DMF solution, and then making up the volume with methanol to obtain a standard curve test solution; (A3) Take 1 mL of 20% piperidine-DMF solution to a 10 mL volumetric flask and dilute to volume with methanol to obtain a blank control; (A4) at 300 nm, measure the absorbance Ai of the standard curve test solution under the blank control to obtain a single-point calibration curve; and obtain the calculation formula of the functional group content as follows: In the formula: b is the sample dilution multiple, M is the molecular weight of the UV leaving group, Mi is the mass of the UV leaving group weighed, in mg; Ai is the absorbance of the UV leaving group, in A; M0 is the mass of the magnetic particle sample weighed, in mg; A0 is the absorbance of the magnetic particle sample, in A.
[0020] B. Sample Testing Weigh 52 mg of COOH magnetic beads A into a test tube, add 19.76 mg of HBTU, 16.64 mg of Fmoc-EDA.HCl and 6.76 mg of DIEA, add 1 mL of DMF, seal, ultrasonicate for 2 min, and shake for 2 h at 25 ° C. After the reaction, take 5 mL of acetonitrile and add it to the test tube. After ultrasonicating for 2 min, magnetic beads are magnetically attracted to the bottom of the test tube, and the upper solution is poured off. Repeat the washing 10 times (measure the UV of the washing solution). 300nm=0.067, and the absorption error of the two washes before and after is consistent). Then the remaining magnetic beads in the test tube are placed in a 65°C oven for drying for 90 minutes. The dried magnetic bead samples A113.2mg and A214.2mg are weighed in parallel into 10mL volumetric flasks, and 1mL of 20% piperidine-DMF solution is added to each of them and shaken on a shaker at 25°C for 30 minutes, and then the volume is fixed with methanol; the samples A1 and A2 to be tested are filtered with a 0.22um NYLON filter membrane, and the absorbance values are determined. The carboxyl contents are obtained by substituting them into the formula and calculating the average values of the parallel samples, respectively. COOH-1 , L COOH-2 , see Table 1.
[0021] Example 2 The content of carboxyl groups in the magnetic particles was determined as follows: A. Preparation of standard curve: weigh 13.4 mg of Fmoc-EDA.HCl, and the rest is the same as step A in Example 1; B. Sample testing: Weigh 50 mg of COOH magnetic beads B in a test tube, add 19 mg HBTU, 16 mg Fmoc-EDA.HCl and 6 mg DIEA, add 1 mL DMF, seal, ultrasonicate for 2 min, and shake for 2 h on a shaker at 25 °C. After the reaction, take 5 mL of acetonitrile and add it to the test tube. After ultrasonicating for 2 min, magnetic beads are magnetically attracted to the bottom of the test tube, and the upper solution is poured off. Repeat the washing for 9 times (measure the UV value of the washing solution). 300nm =0.062, and the absorption errors of the two washes before and after are consistent). Then the remaining magnetic beads in the test tube are placed in a 65°C oven for drying for 90 minutes. The dried magnetic bead samples are weighed in parallel, B11.2 mg and B212.4 mg are respectively weighed into 10 mL volumetric flasks, and 1 mL of 20% piperidine-DMF solution is added to each of them for shaking reaction on a shaker at 25°C for 30 minutes. Then the volume is fixed with methanol, and the samples B1 and B2 to be tested are filtered with a 0.22 um NYLON filter membrane, and the absorbance value is measured. The carboxyl content L is obtained by substituting it into the formula and calculating the average value of the parallel samples. COOH-3 , L COOH-4 , see Table 1.
[0022] Example 3 The content of carboxyl groups in the magnetic particles was determined as follows: A. Preparation of standard curve: weigh 12.6 mg of Fmoc-EDA.HCl, and the rest is the same as step A in Example 1; B. Sample testing: Weigh 50 mg of COOH magnetic beads C in a test tube, add 19 mg HBTU, 16 mg Fmoc-EDA.HCl and 6 mg DIEA, add 1 mL DMF, seal, ultrasonicate for 2 min, and shake for 2 h at 25 ° C. After the reaction, take 5 mL of acetonitrile and add it to the test tube. After ultrasonicating for 2 min, magnetically attract the magnetic ball to the bottom of the test tube, pour off the upper solution, and repeat the washing 8 times (measure the UV of the washing solution). 300nm =0.061, and the absorption errors of the two washes before and after are consistent). Then the remaining magnetic beads in the test tube are placed in a 65°C oven for drying for 90 minutes. The dried magnetic bead samples are weighed in parallel, C110.8 mg and C212.8 mg are respectively weighed into 10 mL volumetric flasks, and 1 mL of 20% piperidine-DMF solution is added to each of them for shaking reaction on a shaker at 25°C for 30 minutes. Then the volume is fixed with methanol, Fmoc-EDA.HCl12.6 mg is weighed, and a standard curve is drawn according to the method of 1.2. The samples C1 and C2 to be tested are filtered with a 0.22 um NYLON filter membrane, and the absorbance values are determined. The carboxyl content L is obtained by substituting it into the formula and calculating the average value of the parallel samples. COOH-5 , L COOH-6 , see Table 1.
[0023] Example 4 The content of hydroxyl in the magnetic beads A is determined as follows: A. Prepare standard curve: weigh 12.4 mg of Fmoc-Leu-OH, and do the same as step A in Example 1; B. Sample testing: Weigh 50.6 mg of the above COOH magnetic beads A into a test tube, add 19.7 mg MSNT, 18 mg Fmoc-Leu-OH and 6 mg Melm, add 1 mL DCM, seal, ultrasonicate for 2 min, and shake for 2 h at 25 ° C. After the reaction, take 5 mL acetonitrile and add it to the test tube. After ultrasonicating for 2 min, magnetic beads are magnetically attracted to the bottom of the test tube, and the upper solution is poured off. Repeat the washing for 9 times (measure the UV of the washing solution). 300nm =0.062, and the absorption errors of the two washings before and after are consistent). Then the remaining magnetic beads in the test tube are placed in a 65°C oven for drying for 90 minutes. The dried magnetic beads samples are weighed in parallel to take 11.0 mg of A3 and 15.8 mg of A4 into 10 mL volumetric flasks, and 1 mL of 20% piperidine-DMF solution is added to each of them for shaking reaction on a shaker at 25°C for 30 minutes. Then the volume is fixed with methanol, and the samples A3 and A4 to be tested are filtered with a 0.22 um NYLON filter membrane, and the absorbance values are measured. The average values of the parallel samples are calculated by substituting them into the formula to obtain the hydroxyl content, which is L OH-1 , L OH-2 , see Table 1.
[0024] Example 5 The content of hydroxyl in the magnetic beads B is determined as follows: A. Preparation of standard curve: Weigh 11.8 mg of Fmoc-Leu-OH, and do the same as step A in Example 1; B. Sample testing: Weigh 50.3 mg COOH magnetic beads B in a test tube, add 19.5 mg MSNT, 18 mg Fmoc-Leu-OH and 6 mg Melm, add 1 mL DCM, seal, sonicate for 2 min, and shake for 2 h at 25 ° C. After the reaction, take 5 mL acetonitrile and add it to the test tube. After sonication for 2 min, magnetic beads are magnetically attracted to the bottom of the test tube, and the upper solution is poured off. Repeat the washing for 9 times (measure the UV of the washing solution). 300nm =0.059, and the absorption errors of the two washings before and after are consistent). Then the remaining magnetic beads in the test tube are placed in a 65°C oven for drying for 90 minutes. The dried magnetic bead samples are weighed in parallel, B3 12.2 mg and B4 13.3 mg, respectively, into 10 mL volumetric flasks, and 1 mL of 20% piperidine-DMF solution is added to each of them for shaking reaction on a shaker at 25°C for 30 minutes. Then the volume is fixed with methanol, and the samples B3 and B4 to be tested are filtered with a 0.22 um NYLON filter membrane. The absorbance values are determined, and the standard sample formula is used to calculate the average value of the parallel samples to obtain the hydroxyl content, L OH-3 , L OH-4 , see Table 1.
[0025] Example 6 The content of hydroxyl in the magnetic beads C is determined as follows: A. Prepare standard curve: weigh 13.4 mg of Fmoc-Leu-OH, and do the same as step A in Example 1; B. Sample testing: Weigh 50.3 mg COOH magnetic beads C in a test tube, add 19.2 mg MSNT, 18.1 mg Fmoc-Leu-OH and 6 mg Melm, add 1 mL DCM, seal, sonicate for 2 min, and shake for 2 h at 25 ° C. After the reaction, take 5 mL acetonitrile and add it to the test tube. After sonication for 2 min, magnetic beads are magnetically attracted to the bottom of the test tube, and the upper solution is poured off. Repeat the washing 8 times (measure the UV of the washing solution). 300nm=0.063, and the absorption errors of the two washings before and after are consistent). Then the remaining magnetic beads in the test tube are placed in a 65°C oven for drying for 90 minutes. The dried magnetic beads samples are weighed in parallel, C3 13.7 mg and C4 14.2 mg are weighed into 10 mL volumetric flasks, and 1 mL of 20% piperidine-DMF solution is added to the shaker at 25°C for 30 minutes. Then the volume is fixed with methanol, and the samples C3 and C4 to be tested are filtered with a 0.22 um NYLON filter membrane. The absorbance values are determined, and the standard sample formula is used to calculate the average value of the parallel samples to obtain the carboxyl content, which is L OH-5 , L OH-6 , see Table 1.
[0026] Comparative Example 1 The detection method was carried out according to Qiu Guangming, Sun Zonghua. Magnetic polymer microspheres covalently bound to neutral proteases [J]. Journal of Biomedical Engineering, 1995(03): 209-213.
[0027] The carboxyl content in the magnetic beads A was detected, and the samples were taken in parallel. The test results were L COOH-7 , L COOH-8 , see Table 2.
[0028] Comparative Example 2 The detection method is the same as that of comparative example 1, and the content of carboxyl groups in the magnetic beads B is detected. Parallel sampling is performed, and the detection results are L COOH-9 , L COOH-10 , see Table 2.
[0029] Table 1 Test results of Examples 1-5 Table 2 Comparative Example 1-2 Test Results As can be seen from Table 1, the parallel experimental results using the Fmoc-fluorescence detection method in Examples 1-5 are stable, with an error of only less than 4%. It can be seen that the sensitivity of detecting the degree of substitution of trace hydroxycarboxyl groups using the method of the present invention is much higher, and although Comparative Examples 1 and 2 can also determine the carboxyl content, the test errors are large and the repeatability and stability are poor. It can be seen from the data in Table 2 that the test method in Comparative Examples 1-2 can no longer detect the hydroxyl content of the sample, so the method of the present invention has extremely high sensitivity and stability.
[0030] In summary, the present invention utilizes the principle that UV leaving groups have fluorescence and can react with functional groups to establish a heterogeneous detection method for functional groups on the surface of magnetic particles. The detection can be completed by simply measuring the reagent supernatant. The test has small error, low detection limit, simple operation, low cost, a wide range of raw material options, strong reproducibility of detection results, and is suitable for magnetic particles coated with polymers with trace amounts of surface carboxyl groups.
Claims
1. A method for detecting the content of functional groups on the surface of magnetic particles, characterized in that: The functional group is a hydroxyl group and / or a carboxyl group, and the detection method comprises the following steps: A. Preparation of standard curve: (A1) Weigh 10-20 mg of UV leaving base into a 50 mL volumetric flask, dissolve it in 5 mL of dissociation agent, place it on a shaker at 25 °C for 30 min, and make up to volume with methanol; (A2) Add 1 mL of the solution obtained in step (A1) to a 10 mL volumetric flask, add 0.9 mL of dissociation agent, and then dilute to volume with methanol to obtain a standard curve test solution; (A3) Take 1 mL of dissociation agent to a 10 mL volumetric flask and dilute to volume with methanol to obtain a blank control; (A4) at 300 nm, measure the absorbance Ai of the standard curve test solution under the blank control to obtain a single-point calibration curve; and obtain the calculation formula of the functional group content as follows: Wherein: b is the sample dilution multiple, M is the molecular weight of the UV leaving group, Mi is the mass of the UV leaving group weighed, in mg; Ai is the absorbance of the UV leaving group, in A; M0 is the mass of the magnetic ball sample weighed, in mg; A0 is the absorbance of the magnetic ball sample, in A; B. Sample testing: (B1) Weigh 50-100 mg of magnetic particle sample into a test tube, add 16-36 mg of UV leaving group, 16-38 mg of condensing agent, 1-2 mL of DMF, and 6-12 mg of catalyst in sequence, seal, ultrasonically disperse for 2-10 min, and then shake at 25° C. for 1-3 h; (B2) Add 5-10 mL of organic solvent to the test tube, ultrasonicate for 2 min, magnetically absorb the magnetic particles to the bottom of the test tube, and pour out the upper solution, and wash repeatedly until the absorbance of the upper solution at a wavelength of 300 nm is less than 0.07, and the absorption error of the two washings is within ±0.005, which determines that the washing is complete, and magnetically recover the magnetic particles and pour out the upper solution; (B3) drying the recovered magnetic particles; (B4) Weigh 10-20 mg of dried magnetic particles into a volumetric flask, add 1-2 mL of dissociation agent, shake and react at 25°C for 30-60 min, then make up to volume with methanol, filter with a 0.2-1 μm filter membrane, and measure the absorbance value, which is the absorbance value A0 of the magnetic sphere sample. Substitute it into the above formula to calculate the content of functional groups.
2. The method for detecting the content of functional groups on the surface of magnetic particles according to claim 1, characterized in that: The functional group is a hydroxyl group, and the UV leaving group is any one of Fmoc-Leu-OH, Fmoc-Ala-OH, Fmoc-Cys(Trt)-OH, Fmoc-Lys(Boc)-OH, and Fmoc-Asp(otBu)-OH.
3. A method for detecting the content of functional groups on the surface of magnetic particles according to claim 2, characterized in that: The UV leaving group is Fmoc-Leu-OH, the condensing agent is MSNT, and the catalyst is Melm.
4. A method for detecting the content of functional groups on the surface of magnetic particles according to claim 3, characterized in that: The added amount of the condensing agent is 19-38 mg.
5. The method for detecting the content of functional groups on the surface of magnetic particles according to claim 1, characterized in that: The functional group is a carboxyl group, and the UV leaving group is any one of Fmoc-EDA.HCl, Fmoc-Cl, and Fmoc-N-Me-EDA(N-Me).HCl.
6. A method for detecting the content of functional groups on the surface of magnetic particles according to claim 5, characterized in that: The UV leaving group is Fmoc-EDA.HCl, the condensing agent is HBTU, and the catalyst is DIEA.
7. A method for detecting the content of functional groups on the surface of magnetic particles according to claim 6, characterized in that: The added amount of the condensing agent is 16-32 mg.
8. A method for detecting the content of functional groups on the surface of magnetic particles according to any one of claims 1 to 7, characterized in that: The dissociation agent is a 20-50% concentration piperidine-DMF solution.
9. A method for detecting the content of functional groups on the surface of magnetic particles according to claim 8, characterized in that: The organic solvent is acetonitrile, tetrahydrofuran, dioxane, acetone, ethanol or methanol.
10. A method for detecting the content of functional groups on the surface of magnetic particles according to claim 9, characterized in that: The filter membrane is made of PES, MCE, NYLON, PP, PTFE or PVDF.